Chloride Dysregulation, Seizures, and Cerebral Edema: A Relationship with Therapeutic Potential. Issue 5 (May 2017) - Glykys, Joseph; Dzhala, Volodymyr; Egawa, Kiyoshi; Kahle, Kristopher T.; Delpire, Eric; Staley, Kevin
Abstract : Pharmacoresistant seizures and cytotoxic cerebral edema are serious complications of ischemic and traumatic brain injury. Intraneuronal Cl − concentration ([Cl − ]i ) regulation impacts on both cell volume homeostasis and Cl − -permeable GABAA receptor-dependent membrane excitability. Understanding the pleiotropic molecular determinants of neuronal [Cl − ]i − cytoplasmic impermeant anions, polyanionic extracellular matrix (ECM) glycoproteins, and plasmalemmal Cl − transporters − could help the identification of novel anticonvulsive and neuroprotective targets. The cation/Cl − cotransporters and ECM metalloproteinases may be particularly druggable targets for intervention. We establish here a paradigm that accounts for recent data regarding the complex regulatory mechanisms of neuronal [Cl − ]i and how these mechanisms impact on neuronal volume and excitability. We propose approaches to modulate [Cl − ]i that are relevant for two common clinical sequela of brain injury: edema and seizures. Trends: Neuronal [Cl − ]i determines how the GABA neurotransmitter will alter the firing pattern of a neuron as well as its cell volume. Thus, understanding the mechanisms that establish, maintain, and regulate neuronal [Cl − ]i are essential if we are to achieve a better understanding of neuronal excitability and cell volume regulation. Neuronal [Cl − ]i is high in some pathological conditions, including cell injury, seizures, and epilepsy. This elevated [Cl − ]i contributes to a lower seizure threshold and altered anticonvulsant efficacy. The cotransport of cations, Cl −, and water may link cytotoxic edema to mechanisms of excitatory GABAA signaling, disinhibition, and increased seizure risk after acute brain injury. New data have emerged demonstrating that intracellular and extracellular immobile anions actually set the neuronal [Cl − ]i, while the Cl − cotransporters effectively facilitate the movement of this anion to reach this set-point. With the recognition of these new determinants of [Cl − ]i we can develop novel approaches to modulate the neuronal [Cl − ]i and volume, and thus treat two of the most common clinical sequela of brain injury: edema and seizures.